2021
DOI: 10.1002/mabi.202100262
|View full text |Cite
|
Sign up to set email alerts
|

Apatite Formation Induced by Chitosan/Gelatin Hydrogel Coating Anchored on Poly(aryl ether nitrile ketone) Substrates to Promote Osteoblastic Differentiation

Abstract: Bone‐like apatite is a promising coating of poly(ether ether ketone) (PEEK) for bone implantation. Poly(aryl ether nitrile ketone) containing phthalazinone moiety (PPENK) is a novel alternative for its easy synthesis. Here, chitosan/gelatin hybrid hydrogel coating is applied to induce the formation of apatite on the surface of PPENK substrate through biomineralization to improve its biocompatibility and osteogenic property. PPENK possessing allyl groups (PPENK‐d) are synthesized and spin‐coated on PPENK substr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 50 publications
(48 reference statements)
0
7
0
Order By: Relevance
“…Firstly, it can induce calcium deposition on the surface of the coating, thus improving the mineralization ability and promoting osteogenesis. Li et al (2021 ) coated the CS/gelatin hydrogel on the poly (aryl ether nitrile ketone)-containing phthalazinone moiety substrate (PPENK) through the spin coating method. Due to the presence of CS, this composite coating can chelate Ca 2+ to promote the deposition of calcium phosphate at the mineral phase on the surface of the PPENK matrix and enhance the biomineralization potential of the coating, which has exhibited biocompatibility and osteogenic properties for MCET3-E1.…”
Section: Application In the Treatment Of Infected Bone Defectsmentioning
confidence: 99%
“…Firstly, it can induce calcium deposition on the surface of the coating, thus improving the mineralization ability and promoting osteogenesis. Li et al (2021 ) coated the CS/gelatin hydrogel on the poly (aryl ether nitrile ketone)-containing phthalazinone moiety substrate (PPENK) through the spin coating method. Due to the presence of CS, this composite coating can chelate Ca 2+ to promote the deposition of calcium phosphate at the mineral phase on the surface of the PPENK matrix and enhance the biomineralization potential of the coating, which has exhibited biocompatibility and osteogenic properties for MCET3-E1.…”
Section: Application In the Treatment Of Infected Bone Defectsmentioning
confidence: 99%
“…Poly­(aryl ether ketone) (PAEK) exhibits the excellent mechanical performances and thermal stability; therefore, using the engineering thermoplastic PAEK as the SMP matrix polymer is expected to satisfy the requirements of mechanical properties and could extend the utilization potential of SMPs in engineering structures. At present, there are several papers investigating the modified shape memory PAEK materials, which mainly focus on the thermoplastic structures and properties. In this paper, metal coordination bonds between pyridine and metal ions were integrated into the PAEK matrix to construct metal-coordinated shape memory PAEK materials. The tuning of the content and species of metal ions was operated to improve the shape memory ability.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure a,b, the cell viability on the surface of all samples reached more than 90%, indicating that the coated PPENK was not cytotoxic. The proliferation assay (Figure c) demonstrated that the cell proliferation on the surface of the samples increased exponentially with time and was not significantly different from the remaining samples, proving that the samples did not promote cell proliferation …”
Section: Resultsmentioning
confidence: 99%
“…The proliferation assay (Figure 5c) demonstrated that the cell proliferation on the surface of the samples increased exponentially with time and was not significantly different from the remaining samples, proving that the samples did not promote cell proliferation. 53 The effect of the apatite coating on the properties of the PPENK surface was then investigated by cell adhesion and viability assays. 54 After 1, 2, and 3 days of cultivation of cells onto the sample surface, a live/dead staining of the cells on sample surface was performed.…”
Section: Effect Of 3d Nanoporousmentioning
confidence: 99%